Comparison of Prevalence of Pre-Diabetes and Type-2 Diabetes Mellitus Between Athletes and Non-Athletes - Muhammad Irfan; Fatima Abid; Sassi Kanwal; Aliya Jafri; Padma Rathore; Noor un Nisa Memon (Pakistan Journal of Medicine and Dentistry)
Background: Sports and Exercise activities are exceedingly advantageous for the human body and extremely helpful in decreasing the risks of diseases. The purpose of this research was to know the prevalence of pre-diabetes and Type 2 diabetes mellitus among athletes and non-athletes.